Successful Pregnancy with Terminal Renal Failure: Fiction or Reality (on the Example of Clinical Observation) - A. D. Vishnyak; A. N. Karimova; Yu. A. Kulai; M. V. Chernobai; V. R. Kofeeva; G. M. Khairullina; E. T. Mullayarova; A. G. Isaeva (SINAPS LLC, 2023)
195 million women on Earth suffer from chronic kidney disease - some of them are planning to become mothers. Even in absolutely healthy women, pregnancy is fraught with risks. These risks increase when it comes to kidney pathology. It is known that pregnancy in women with kidney diseases, even with preserved renal function, is accompanied by serious problems for both the mother and the fetus. We present a clinical observation of a 23-year-old patient with terminal renal insufficiency who successfully carried out the pregnancy. The patient's polymorbid condition (chronic kidney disease, ulcerative colitis, anemia, etc.) required complex therapy and an interdisciplinary approach, which was implemented from the first days of the woman's observation. The highly professional work of a team of specialists (nephrologists, resuscitators, obstetricians-gynecologists, gastroenterologists, infectious disease specialists, functional diagnostics doctors, urologists, etc.) determined the successful outcome of this observation. The article focuses on the factors aggravating this observation, as well as determining, on the contrary, a favorable outcome.